Factors influencing actual usage of fitness tracking devices: Empirical evidence from the UTAUT model. Issue 1 (2nd January 2023) - Mishra, Anubha; Baker-Eveleth, Lori; Gala, Prachi; Stachofsky, Julia
Abstract: This research investigates factors influencing the actual usage of wearable fitness devices. Based on the Unified Theory of Acceptance and Use of Technology, the authors propose that privacy concerns, social influence, data accuracy, device engagement, and user efficacy impact the actual usage of wearable fitness devices via performance and effort expectancy. Based on 124 responses using the structural equation approach, most hypotheses were supported. The social influence had the strongest indirect effect through performance expectancy, while user efficacy had the strongest indirect effect through effort expectancy. Data accuracy and device engagement had a positive influence on actual usage and privacy concerns negatively affected the device's use.